(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article is a theoretical essay on the need for somatic education that enables reconnection with the knowledge of the body, from its materiality, for the continuous activation of a vital eroticism that creates new modes of existence and reconfigures the powers of presence and action of the body with the environment. The article is an offshoot of the author’s doctoral thesis and dialogues with references from the fields of biology, feminist philosophy, and somatic practices, such as Vinciane Despret, Bonnie Bainbridge Cohen, Silvia Federici, among others.